2018
DOI: 10.1016/j.jbankfin.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Subjectivity in sovereign credit ratings

Abstract: A sovereign credit rating is a function of hard and soft information that should reect the creditworthiness and the probability of default of a country. We propose an alternative characterisation for the subjective component of a sovereign credit rating the parts related to the ratee's lobbying eort or its familiarity from a United States point of view and apply it to S&P, Moody's and Fitch ratings, using both traditional ordered-logit panel models and machine learning techniques. This subjective component tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 45 publications
2
32
0
1
Order By: Relevance
“…The findings agree with the analysis done by Mellios and Paget-Blanc (2006) and Chee et al (2015) and concluded that exchange rates are one of the variables used by rating agencies to measure a country's creditworthiness. The results are consistent with findings by Bissoondoyal and Bheenick (2005); Mellios and Paget-Blanc (2006); Iyengar (2010); Afonso et al (2011); Arefjevs and Brasliņs (2013);Sánchez-Monedero et al (2014); Kabadayi and Celik (2015); Ivanovic et al (2015); Chee et al (2015);De Moor et al (2018); and Cantor and Packer (1996) that GDP growth is a crucial variable in determining sovereign credit ratings. For CPIH, there seems to be less difference between the means for less stable and those for more stable.…”
Section: Naïve Bayes Model For Moody'ssupporting
confidence: 90%
“…The findings agree with the analysis done by Mellios and Paget-Blanc (2006) and Chee et al (2015) and concluded that exchange rates are one of the variables used by rating agencies to measure a country's creditworthiness. The results are consistent with findings by Bissoondoyal and Bheenick (2005); Mellios and Paget-Blanc (2006); Iyengar (2010); Afonso et al (2011); Arefjevs and Brasliņs (2013);Sánchez-Monedero et al (2014); Kabadayi and Celik (2015); Ivanovic et al (2015); Chee et al (2015);De Moor et al (2018); and Cantor and Packer (1996) that GDP growth is a crucial variable in determining sovereign credit ratings. For CPIH, there seems to be less difference between the means for less stable and those for more stable.…”
Section: Naïve Bayes Model For Moody'ssupporting
confidence: 90%
“…Traditional approaches to modelling credit ratings rely on parametric estimations (such as ordered response models or OLS; see for example, Cantor & Packer 1996;Afonso et al, 2009;Baghai et al, 2016). However, due to the non-linearity of ratings and their distributional properties, and to address multicollinearity, researchers have considered non-parametric approaches to model sovereign ratings (Bennell et al, 2006;De Moor et al, 2018;Fioramanti, 2008;Markellos et al, 2016;Ozturk et al, 2016). The central benefits associated with these approaches are much better handling of non-linear outcomes in the data (Markellos et al, 2016) and the potential for superior fit (De Moor, 2018).…”
Section: Reconstructing Sovereign Credit Ratingsmentioning
confidence: 99%
“…However, due to the non-linearity of ratings and their distributional properties, and to address multicollinearity, researchers have considered non-parametric approaches to model sovereign ratings (Bennell et al, 2006;De Moor et al, 2018;Fioramanti, 2008;Markellos et al, 2016;Ozturk et al, 2016). The central benefits associated with these approaches are much better handling of non-linear outcomes in the data (Markellos et al, 2016) and the potential for superior fit (De Moor, 2018). Because sovereign ratings may be subject to thresholds in country-level predictors, such as GDP per capita (S&P 2017), methods capable of handling non-linearities are essential.…”
Section: Reconstructing Sovereign Credit Ratingsmentioning
confidence: 99%
“…Some authors state that a sovereign credit rating is a function of basic data and about information that is difficult to measure which should reflect the creditworthiness and the probability of a country to default. They propose an alternative characterisation for the subjective component of a sovereign credit rating -the part related to the rate's lobbying effort or its familiarity from a United States point of view -and apply it to S&P and Moody's and Fitch ratings, using both traditional ordered logit panel models and machine learning techniques (De Moor et al 2018). In the paper of Daud and Podivinsky (2011), it is found that the positive effect of the accumulation of reserves aiming to improve sovereign ratings is crowded out by the negative effect of the accumulation of external debt, resulting in a net negative effect.…”
Section: Literature Reviewmentioning
confidence: 99%